EFFECTS OF AMLODIPINE, FOSINOPRIL AND METOPROLOL ON HEMODYNAMICS IN HYPERTENSIVE PATIENTS - A. L. Hohlov; M. I. Shunikova; A. Yu. Sosnin; I. N. Kagramanyan; L. A. Lisenkova (Столичная издательская компания, 2015)
Aim. To assess an efficacy of antihypertensive therapy with calcium antagonist, angiotensin converting enzyme inhibitor and β-blocker in patients with arterial hypertension (AH) taking into account influence on central and peripheral hemodynamics. Material and methods. 60 patients with AH of I-II stage, 1-2 grade were studied. They were split in 3 groups. Patients of the first group received amlodipine (Tenox), 5-10 mg/d, the second group - fosinopril (Monopril), 10-20 mg/d and the third group - metoprolol (Metocard), 50-200 mg/d. Diuretics were added when necessary. Ambulatory blood pressure (BP) monitoring, echocardiography, ultrasound investigation of brachiocephalic and main cerebral arteries, test on reactive hyperemia and nitroglycerine were conducted before and after 6 months of therapy. Results. Amlodipine, fosinopril and metoprolol had similar antihypertensive effect. Amlodipine was more effective in comparison with fosinopril and metoprolol in reduction of left ventricular (LV) myocardial mass and improving of LV diastolic function. Amlodipine and fosinopril had positive effect on vascular remodeling. Metoprolol reduced in BP morning elevation and heart rate, but had no effect on systolic BP variability. Conclusion. Amlodipine, fosinopril and metoprolol have similar antihypertensive effect but different influence on the heart, arteries, BP variability and hemodinamics.